Global Dermatophyte Infections Linked to Human and Animal Health: A Scoping Review - Aditya K. Gupta; Tong Wang; Susmita; Mesbah Talukder; Wayne L. Bakotic (Microorganisms)
Dermatophytes are commonly encountered pathogens in clinical practice causing superficial infections of the skin, hair, and nails. These pathogens are often found on animals such as livestock (e.g., cattle, rabbits) and pets (e.g., cats, hedgehogs) that can lead to spillover infections in human populations. Here, we reviewed published reports (2009–2024) of dermatophyte infections in animals and in humans with a history of animal contact. A literature search was completed in October 2024 using PubMed, Embase (Ovid), and Web of Science (Core Collection), which identified 250 articles. Generally, dermatophytes tend to infect younger animals with long hair and exhibit a species-specific host range. Microsporum canis was the most commonly reported species—linked to cats—that can cause tinea capitis, especially concerning the development of kerion in children. Trichophyton verrucosum is strongly associated with cattle. The Trichophyton mentagrophytes complex shows a diverse range of animal hosts, with rabbits being most frequently reported; however, T. mentagrophytes var. erinacei is almost exclusively isolated from hedgehogs, and T. mentagrophytes var. benhamiae is more commonly found on rodents (e.g., guinea pigs). Lastly, the geophilic Nannizia gypsea has been isolated from both dogs and cats. Managing dermatophyte zoonoses is an ongoing challenge, as healthcare providers may empirically treat with corticosteroids or antibacterial agents due to its atypical inflammatory appearance. Evidence of in vitro resistance against griseofulvin and fluconazole has been documented in multiple zoonotic dermatophyte species. Resistance development against terbinafine and itraconazole is also a possibility, although the number of reports is scarce. Under the principles of the One Health approach, research on human fungal diseases should take animal and environmental factors into account. A renewed call for increased testing efforts is warranted.